i-PRESTIGE : 2020 Annual Report Research, Industrial Linkages and Alumni Division UiTM Cawangan Johor - Mohamed Abdul Kadir, Juliana; Sa'udah@Suhadak, Nurulzulaiha; Sukar, Muhamad Ashaari; Ismail, Noriah; Samsudin, Aidarohani; Mazan, Diana'; Isahak, Siti Nordiyana; Abu Bakar, Azinoor Azida; Wee, Lee Siong; Abdol Rahim @Ibrahim, Abdul Hadi; Abdullah, Mohammad; Mohamed, Suhana; et al. (Research, Industrial Linkages and Alumni Division UiTM Cawangan Johor, 2020)
All rights reserved. No part of this publication may be reproduced, stored transmitted in any form or by any means, by any individual, department, or organization without the prior written permission from the Research, Industrial Linkages, and Alumni Division (PJI&A) of Universiti Teknologi MARA Cawangan Johor.